2023
DOI: 10.1002/hed.27417
|View full text |Cite
|
Sign up to set email alerts
|

Head and neck solitary fibrous tumors: A review of the National Cancer Database

Abstract: Background Head and neck solitary fibrous tumors (SFTs) are rare neoplasms, with few large‐scale studies describing this entity. We evaluated the demographics and correlates of survival in a large series of SFT patients. Methods The 2004–2017 National Cancer Database was queried for head and neck SFT patients receiving definitive surgery. Cox proportional‐hazards and Kaplan–Meier analyses assessed overall survival (OS). Results Of 135 patients, sinonasal (33.1%) and orbital (25.9%) SFTs were most common. Appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
2
0
1
Order By: Relevance
“…However, in selected cases, primary or adjunctive radiotherapy and/or chemotherapy might still be considerable. Possible indications may include malignancy with infiltrative growth or disseminated metastases, postoperative positive margins with no possibility of resectability, or severe paraneoplastic syndromes [ 46 50 ]. De Boer et al were able to demonstrated in a case of paraneoplastic active SFT that combined chemoradiotherapy with embolization can reduce tumor size and hormone activity to achieve resectability [ 19 ].…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…However, in selected cases, primary or adjunctive radiotherapy and/or chemotherapy might still be considerable. Possible indications may include malignancy with infiltrative growth or disseminated metastases, postoperative positive margins with no possibility of resectability, or severe paraneoplastic syndromes [ 46 50 ]. De Boer et al were able to demonstrated in a case of paraneoplastic active SFT that combined chemoradiotherapy with embolization can reduce tumor size and hormone activity to achieve resectability [ 19 ].…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…Analysis of the SEER database showed that surgery plus chemotherapy improved survival to a greater extent than chemotherapy alone, although the outcomes of surgery alone were more favorable 1014 . Skull base origin conferred worse prognosis as compared to sinonasal primary site 1015 . Multiple different chemotherapeutic agents have been used with overall poor response rates, regardless of whether they were first‐, second‐, or third‐line treatments 1016,1017 .…”
Section: Other Rare Benign Neoplasms and Lesionsmentioning
confidence: 99%
“…Da diese Läsionen häufig eine perivaskuläre Infiltration mit Zellnestern maligner Zellen entlang von Blutgefäßen aufweisen, oftmals bis weit außerhalb der sichtbaren Tumorgrenzen, ist es manchmal schwierig, den Tumor komplett zu entfernen. Alternativ ist eine primäre Strahlenbehandlung, Chemotherapie oder Immuntherapie zu diskutieren [391,392].…”
Section: Maligne Gefäßtumoreunclassified